Mass spectrometric dereplication of nitrogen-containing constituents of black cohosh (Cimicifuga racemosa L.) - Nikolić, Dejan (2011)
Black cohosh preparations are popular dietary supplements among women seeking alternative treatments for menopausal complaints. For decades, triterpene glycosides and phenolic acids have dominated the phytochemical and biomedical research on this plant. In this study, we provide evidence that black cohosh contains an unexpected and highly diverse group of secondary nitrogenous metabolites previously unknown to exist in this plant. Using a dereplication approach that combines accurate mass measurements, database searches and general knowledge of biosynthetic pathways of natural products, we identified or tentatively identified 73 nitrogen-containing metabolites, many of which are new natural products. The identified compounds belong to several structural groups including alkaloids, amides or esters of hydroxycinnamic acids and betains. Among the alkaloids, several classes such as guanidino alkaloids, isoquinolines and β-carbolines were identified. Fragmentation patterns for major compound classes are discussed, which provides a framework for the discovery of these compounds from other sources. Identification of alkaloids as a well-known group of bioactive natural products represents an important advance in better understanding of the pharmacological profile of black cohosh.